Integrating the social reproduction of labor into macroeconomic theory: Unpaid caregiving and productivity in paid production - Mark Setterfield (Levy Economics Institute of Bard College, 2025)
The purpose of this paper is to contribute to the integration of unpaid caregiving in the household into short- and long-term macroeconomic theory and, in particular, the theoretical structure of production on the supply side of the economy. The ambition of the project is to furnish a general theoretical representation of how unpaid caregiving and its (gendered) social structure contribute to the technical conditions of production in the sphere of marketed output. In so doing, it aims to provide macro theorists with an apparatus that allows consistent description of both short-term (levels of activity) and long-term (rates of growth) macro outcomes in a manner that routinely integrates feminist insights regarding the gendered structure of the social reproduction of labor into macroeconomic analysis.
Keywords: E11; E12; B54; E23; J13; J16; J24; O33; 330; Social reproduction of labor; unpaid caregiving; macroeconomic theory; potential output; natural rate of growth; technical change